2021
DOI: 10.1155/2021/1942674
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Depressive Disorder among Prisoners in Mekelle General Prison Center, Tigray, Ethiopia: A Cross-Sectional Study Design

Abstract: Background. Depression is the most prevalent mental disorder among prisoners and is the second leading cause of disability worldwide. Depression affects more for those who are less educated, female, single, and young prisoners, and worldwide prevalence of depression among prisoners is 10.2% and 14% for male and female prisoners, respectively. However, a study conducted on prevalence of depression and associated factors is scarce in Ethiopia (Tigray) despite there is high magnitude. Methodology. An institution-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 34 publications
0
12
2
Order By: Relevance
“…However, this findings is higher than the studies conducted in Northwest Amhara (43.8%) [ 24 ], Jimma Town (41.9%) [ 8 ], in Nigerian (42.2%) [ 16 ], in Iran (29%) [ 15 ], and in France (17.9%) [ 14 ]. On the contrary the prevalence obtained from this study was lower than the studies done in Hawassa Town (56.4%) [ 17 ], Mekelle Ethiopia (55.9%) [ 26 ], and Malaysia (55.4%) [ 13 ]. The above variations could be explained by differences in the tool used to measure depression, the cut of value, the study settings, the length of sentenced year difference, and differences in the environmental characteristics of prisons.…”
Section: Discussioncontrasting
confidence: 94%
“…However, this findings is higher than the studies conducted in Northwest Amhara (43.8%) [ 24 ], Jimma Town (41.9%) [ 8 ], in Nigerian (42.2%) [ 16 ], in Iran (29%) [ 15 ], and in France (17.9%) [ 14 ]. On the contrary the prevalence obtained from this study was lower than the studies done in Hawassa Town (56.4%) [ 17 ], Mekelle Ethiopia (55.9%) [ 26 ], and Malaysia (55.4%) [ 13 ]. The above variations could be explained by differences in the tool used to measure depression, the cut of value, the study settings, the length of sentenced year difference, and differences in the environmental characteristics of prisons.…”
Section: Discussioncontrasting
confidence: 94%
“…According to one study, those who reported a poor prison meal were more than twice as likely to develop depression as those who reported a good prison meal. [ 12 ] Hence, it is necessary to evaluate and address the living conditions of jail to ensure the adequate functioning of prisoners.…”
Section: Discussionmentioning
confidence: 99%
“…Besides this, depression is found as the main cause of disability among prisoners accounting for 18% of all cases. [ 12 ] Despite the severity of the problem, there is a dearth of studies available on prisoners assessing the prevalence of depression in Odisha. Thus, the findings of this study will be beneficial for both the prison inmates and policymakers to design better policies and interventions and to bring out new reformation in prison for the mental well-being of the prison inmates.…”
Section: Introductionmentioning
confidence: 99%
“…They show a higher sensitivity to anxiety with higher rates of generalized anxiety disorders and panic attacks (16,17). However, other studies presented conflicting data regarding the differences between these two groups challenging the idea of a particular effect of first imprisonment on the psychological well-being of detained persons (18)(19)(20)(21). To get better insight into this issue, the present study investigates FTI and RLTI cases with psychiatric disorders admitted to an acute care ward located in the central prison of Geneva, Switzerland.…”
Section: Introductionmentioning
confidence: 96%